Kimberlite durability: geotechnical input into Jwaneng underground mining studies - Kebatsetse, L.Q.; Maphane, K.; Dunn, M.J.; Bushula, E. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Jwaneng D/K2 mine has started its transition into an underground mine through development of twin declines that started in May 2024. First carats production from the underground mine is expected around 2036. Block caving, sublevel caving and other caving-related methods are being studied for potential use in the exploitation of the Jwaneng underground resource. Jwaneng mine initiated analysis of swelling clays as part of geotechnical inputs into mining studies. Relationships between occurrence of swelling clays and rock durability/strength are a widely known phenomenon in mining and construction industries. The presence of swelling clays of various proportions in kimberlite rocks poses several technical and operational issues that need to be managed in an underground mine. Understanding intricacies between the rock swelling behaviour and strength, and overall deformation in response to excavation, is critical as an input into the kimberlite underground mine design and operation. Jwaneng mine determined the presence of swelling clays (smectite group) in various kimberlite facies (volcaniclastic kimberlite and pyroclastic kimberlite) using the X-ray diffraction methodology. The swelling clay results were then compared to known durability tests – field weathering test, Slake Durability Index and accelerated weathering index – in an endeavour to determine the impact of swelling clay on durability. Kimberlite durability is an important consideration of both design and operation caving mines on such aspects as oredrive design, ground support design, rehabilitation strategies, draw control strategies and mud rush risks. This paper summarises the work undertaken to date in characterising the Jwaneng D/K2 kimberlites, with a specific focus on swelling clays proportions and expected behaviour.